Cotylidia fibrae (Rickenellaceae, Hymenochaetales), a new species from China - Yang, Cheng; Xu, Yu-Yan; Fan, Li (Phytotaxa, 2021)
Cotylidia fibrae sp. nov. is described and illustrated from north China. Morphologically, the new species is distinguished from other Cotylidia species by the combination of a light grayish yellow pileal margin and pileal and hymenophore coverings of distinct white fibres. Molecular phylogenetic analyses based on ITS and nrLSU sequences are provided, which supports the position of the new species. A key is provided to the Cotylidia species known worldwide.